Canine Pyothorax: Comparison of Culture and Susceptibility Results to the BSAVA PROTECT ME Poster and Other Published Recommended Antimicrobial Use Guidelines - Iris Heinsoo; David J. Walker; Kine Bergum Hjellegjerde; Julia W. Y. Tang; Alison L. Moores (Animals, 2023)
The most common bacterial isolates in dogs with pyothorax include mixed anaerobes, Enterobacteriaceae (especially Escherichia coli), Pasteurella spp., Streptococcus spp., and Staphylococcus spp. A fluoroquinolone with amoxicillin (±clavulanate) or a fluoroquinolone with clindamycin are the most commonly recommended empirical antimicrobials whilst pending bacterial culture of the pleural effusion. The aim of this study is to review and compare the pleural effusion culture and antimicrobial susceptibility results to the PROTECT ME poster and other published antimicrobial use guidelines. The medical records of 53 dogs diagnosed with pyothorax between 2014 and 2020 at two veterinary referral centres were reviewed. Information, including culture and susceptibility results, was assessed. Antimicrobial susceptibility panels varied; susceptibility to a particular antibiotic was calculated as a percentage of isolates tested against the same antibiotic. A total of 30 of 53 dogs (57.7%) had a positive pleural fluid culture. The most common isolates were Pasteurella species (23.3%), Escherichia coli (23.3%), and mixed anaerobes (20%). From the aerobic isolates, 73–83% were susceptible to a fluoroquinolone, 14/19 (74%) to amoxicillin, and 20/22 (91%) to potentiated amoxicillin. Resistance to clindamycin was documented in 9/13 (69%) aerobic isolates, with all Gram-negative bacteria (9/9) being resistant. The combination of potentiated amoxicillin with marbofloxacin would have been appropriate in most of the dogs (75–92.9%). This study shows a high rate of resistance to clindamycin, which is not a suitable option for monotherapy and may be less effective in combination therapy compared to potentiated amoxicillin.